Methods and ways of translating the realities of the kazakh national culture into chinese on the material of the novel “Abay’s Way” by Mukhtar Auezov (Journal of Oriental Studies, 2022)
The novel «Abay’s way» has deep cultural significance and research value, as it is one of the worksthat comprehensively reflects the traditional culture of the Kazakh people through records of the life ofthe Abai family. The purpose of this article is to review the methods and ways of translating the realitiesof Kazakh national culture into Chinese based on the materials of the novel «Abay’s way» by MukhtarAuezov. The analysis of the main methods of translating the realities of Kazakh culture into Chinese is ofpractical importance for further study in the framework of translation theory, as well as sciences such asphilology, cultural studies, and literary studies.To study this topic, methods of systematic and comparative analysis, as well as the method of gen-eralization and abstraction were used. As a result of the analysis, it was revealed that when translatingthese realities into Chinese, the translator used such translation methods as descriptive translation, trans-literation, word substitution, and the method of word omission.The research materials can be used as additional literature on disciplines related to the teaching oftranslation studies, languages, and literature.Key words: descriptive translation, transliteration, native language, Kazakh culture, Kazakh soul.